Choledochoduodenostomy: indications, technique and results - Suiffet, Walter; Ituño, Carlos (Cirugía del Uruguay, 1974)
The author's experience with choledochoduodenostomyes is based on a series of 28 patients. He starts by a chronological outline of this procedure. It is a valuable too! in the, treatment of multiple residual and/or recurrent choledocholithiasis, cholangitis and subacute or associated chronic pancreatitis, and more specially so in the case of elderly patients, in reoperations of the biliary t ract and in those cases where risk is considerable. Technical details and objections to its application are listed. The author concludes that is an advisable procedure. It does create a pathological condition, but it helps to eliminate biliary disease which is worse. Results obtained ·have been excellent.